Europe 2020 And Cohesion Policy. Implications For Transition Regions. The Case Of Andalusia - Francisco Yépez Mu\~noz (European Regional Science Association (ERSA), 2012)
European Cohesion Policy has traditionally been considered as a useful tool to advance in the economic integration of the European Union by helping less developed regions in their convergence process with more developed ones. Nowadays European Cohesion Policy and Structural Funds are one of the main instruments of intervention of EU authorities, so it is being used more and more in relation with other european policies and not only for its original purpose of balancing economic differences among regions. The aim of this paper is to analyze, through the particular case of Andalusia, the impact of the strategy Europe 2020 and its translation to the new Regulations of Cohesion Policy proposed by the European Commission on October 6, 2011, in regions traditionally beneficiaries of European Cohesion Policy. This analysis should be understood in the context of one of the most serious economic crisis in recent years, which has particularly affected some of priority regions for Cohesion Policy, as it is the case of Andalusia.
Keywords: H54; R58; 330; Cohesion Policy; Regional Economics; Regional Policy; Europe 2020